Pengaruh Penambahan Udang Rebon Kering terhadap Peningkatan Kandungan Protein dan Uji Organoleptik Pada Sate Aci - Antosias; Wadli, Yunika Purwanti; Daryono (Fakultas Pertanian, Universitas Warmadewa, 2023)
Sate aci made from tapioca flour can be given culinary variations by adding dried rebon shrimp which can enrich the flavour and nutrients contained in it. Especially the protein content in dried rebon shrimp can increase the nutritional quality of aci satay. This study aims to see the effect of the addition of dried rebon shrimp on the increase in protein and organoleptic tests on aci satay with 4 parameters namely colour, aroma, texture and taste. The making of dried rebon shrimp aci satay with 6 treatments of dried rebon shrimp addition (0 g, 10 g, 20, g, 30 g, 40 g and 50 g) will be tested by kjeldahl method to determine the protein content and taste test to 30 panellists. This research design applies a completely randomised design with 4 replications. Sate aci without the addition of dried rebon shrimp will be used as a control. The results of this study showed an increase in protein content in dried rebon shrimp aci satay with the highest value of 7.26% in the treatment of adding dried rebon shrimp 50 grams. Organoleptic test results from the most preferred and accepted panellists were in the treatment of adding 10 grams of dried rebon shrimp.